Inhibiting amyloid beta (1–42) peptide-induced mitochondrial dysfunction prevents the degradation of synaptic proteins in the entorhinal cortex - Olajide, Olayemi Joseph; La Rue, Claudia; Bergdahl, Andreas; Chapman, Clifton Andrew (Frontiers in Aging Neuroscience, 2022)
Increasing evidence suggests that mitochondrial dysfunction and aberrant release of mitochondrial reactive oxygen species (ROS) play crucial roles in early synaptic perturbations and neuropathology that drive memory deficits in Alzheimer’s disease (AD). We recently showed that solubilized human amyloid beta peptide 1-42 (hAβ1-42) causes rapid alterations at glutamatergic synapses in the entorhinal cortex (EC) through the activation of both GluN2A- and GluN2B-containing NMDA receptors. However, whether disruption of mitochondrial dynamics and increased ROS contributes to mechanisms mediating hAβ1-42-induced synaptic perturbations in the EC is unknown. Here we assessed the impact of hAβ1-42 on mitochondrial respiratory functions, and the expression of key mitochondrial and synaptic proteins in the EC. Measurements of mitochondrial respiratory function in wild-type EC slices exposed to 1 µM hAβ1-42 revealed marked reductions in tissue oxygen consumption and energy production efficiency relative to control. hAβ1-42 also markedly reduced the immunoexpression of both mitochondrial superoxide dismutase (SOD2) and mitochondrial-cytochrome c protein but had no significant impact on cytosolic-cytochrome c expression, voltage-dependent anion channel protein (a marker for mitochondrial density/integrity), and the immunoexpression of protein markers for all five mitochondrial complexes. The rapid impairments in mitochondrial functions induced by hAβ1-42 were accompanied by reductions in the presynaptic marker synaptophysin, postsynaptic density protein (PSD95), and the vesicular acetylcholine transporter, with no significant changes in the degradative enzyme acetylcholinesterase. We then assessed whether reducing hAβ1-42-induced increases in ROS could prevent dysregulation of entorhinal synaptic proteins, and found that synaptic impairments induced by hAβ1-42 were prevented by the mitochondria-targeted antioxidant drug mitoquinone mesylate, and by the SOD and catalase mimetic EUK134. These findings indicate that hAβ1-2 can rapidly disrupt mitochondrial functions and increase ROS in the entorhinal, and that this may contribute to synaptic dysfunctions that may promote early AD-related neuropathology.